Greater-omentum lesion-score (GOLS) as a predictor of residual disease in different regions of the peritoneal cavity in patients undergoing interval cytoreductive surgery for advanced ovarian cancer and its potential clinical utility. Issue 11 (November 2021) - Bhatt, Aditi; Kammar, Praveen; Rousset, Pascal; Sinukumar, Snita; Mehta, Sanket; Parkih, Loma; Goswami, Gaurav; Shaikh, Sakina; Kepenkian, Vahan; Bakrin, Naoual; Devouassoux-Shisheboran, Mojgan; Glehen, Olivier
Abstract: Background and aim: The greater omentum(GO) is a common site of residual disease in patients receiving neoadjuvant chemotherapy for advanced epithelial ovarian cancer. The presence of tumor in the GO could predict presence of disease in other peritoneal regions. The goal of this study was to perform a correlation between the greater-omentum lesion-score(GOLS) and presence of disease in different peritoneal regions and determine its potential utility in guiding interval cytoreductive surgery(CRS). Methods: This prospective study included 134 patients undergoing interval CRS from July 1, 2018 to June 30, 2020. Each region of Sugarbaker's Peritobneal Cancer Index(PCI) was given a lesion score(LS) from 0 to 3 according to the diameter of the largest tumor in the region. The GOLS was recorded separately from other structures in the region. Correlation between the GOLS and surgical and pathological LS in each region was performed. Results: As the GOLS increased, the incidence of disease(surgical LS) in other regions of the peritoneal cavity increased. Receiver operating characteristic(ROC) curves showed area under curve more than 80% for regions 1–2 and 7–8 indicating a high probability of disease in these regions in patients with GOLS 1–3. The positive predictive value(PPV) of preoperative imaging for GOLS was 95.7%. No cut-off of the GOLS could predict presence of disease on pathology with more than 70% accuracy. Conclusions: Presence of disease in the GO warrants performing upper abdominal exploration and/or cytoreduction and interval CRS should be planned accordingly in these patients. Imaging has a high PPV in detecting disease in the GO. Highlights: GOLS can predict the probability of residual disease in other peritoneal regions GOLS of 1–3 is predictive of disease in regions 1–2 and 7–8 in 80% of the patients GOLS 1–3 warrants performing upper-abdominal exploration/cytoreduction Imaging had a 95.7% positive predictive value for detecting disease in the greater-omentum GOLS showed a poor correlation(<70%) with the pathological lesion score